Designation Products: Boron Neutron Capture Therapy for Head and Neck Carcinoma. (18th May 2021) - Kanno, Hitoshi; Nagata, Hironori; Ishiguro, Akihiro; Tsuzuranuki, Satoshi; Nakano, Shintaro; Nonaka, Takahiro; Kiyohara, Koushin; Kimura, Toshinari; Sugawara, Akihiko; Okazaki, Yuzuru; Takae, Shinichi; Nakabayashi, Tetsuo; et al.
Abstract: : The Japanese Ministry of Health, Labour and Welfare approved a drug called borofalan ( 10 B), a treatment system, and a dose calculation program for boron neutron capture therapy (BNCT) in March 2020. The application pertaining to the products submitted to the Pharmaceuticals and Medical Devices Agency was supported by a Japanese, open-label, uncontrolled trial (Study 002) in patients with unresectable, locally recurrent head and neck squamous cell carcinoma after chemoradiotherapy or radiotherapy, or in those with unresectable locally advanced or locally recurrent (LA/LR) head and neck nonsquamous cell carcinoma. The drug was administered as a single intravenous dose using infusion rates of 200 mg/kg per hour for the first 2 hours after the start of administration and 100 mg/kg per hour during irradiation. Neutron irradiation was performed using the devices at a single dose of 12 Gy-equivalent for oral, pharyngeal, or laryngeal mucosa for up to 60 minutes from 2 hours after the start of drug administration. The primary endpoint was the overall response rate (ORR). The results of Study 002 showed that the ORR based on an assessment of the Independent Central Review Committee per RECIST version 1.1 was 71.4% (90% confidence interval [CI], 51.3%–86.8%). The lower limit of the 90% CI exceeded the prespecified threshold for ORR. When BNCT is applied to patients with unresectable LA/LR head and neck cancer, precautions should be taken, and patients should be monitored for possible onset of dysphagia, brain abscess, skin disorder, crystal urine, cataract, and/or carotid hemorrhage. Implications for Practice: Borofalan ( 10 B), a treatment system and a dose calculation program for boron neutron capture therapy (BNCT), demonstrated significant efficacy in an open-label, uncontrolled trial in which overall response rate was the primary endpoint for patients with unresectable locally advanced or locally recurrent head and neck cancer. Although no information about survival benefits was obtained, BNCT will become an effective treatment option that is expected to manage local lesions that are intractable with any standard therapy. In addition, BNCT is expected to maintain quality of life of the intended patient population, on account of its high tumor selectivity and low invasiveness. Abstract : This article summarizes the regulatory review of data leading to the approval of borofalan in Japan.